SARS-CoV-2 Serosurveys: How Antigen, Isotype and Threshold Choices Affect the Outcome. (31st October 2022) - Binder, Raquel A; Fujimori, Gavin F; Forconi, Catherine S; Reed, George W; Silva, Leandro S; Lakshmi, Priya Saikumar; Higgins, Amanda; Cincotta, Lindsey; Dutta, Protiva; Salive, Marie-Claire; Mangolds, Virginia; Anya, Otuwe; et al.
Abstract: Background: Evaluating the performance of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) serological assays and clearly articulating the utility of selected antigens, isotypes, and thresholds is crucial to understanding the prevalence of infection within selected communities. Methods: This cross-sectional study, implemented in 2020, screened PCR–confirmed coronavirus disease 2019 patients (n = 86), banked prepandemic and negative samples (n = 96), healthcare workers and family members (n = 552), and university employees (n = 327) for anti–SARS-CoV-2 receptor-binding domain, trimeric spike protein, and nucleocapsid protein immunoglobulin (Ig)G and IgA antibodies with a laboratory-developed enzyme-linked immunosorbent assay and tested how antigen, isotype and threshold choices affected the seroprevalence outcomes. The following threshold methods were evaluated: (i) mean + 3 standard deviations of the negative controls; (ii) 100% specificity for each antigen-isotype combination; and (iii) the maximal Youden index. Results: We found vastly different seroprevalence estimates depending on selected antigens and isotypes and the applied threshold method, ranging from 0.0% to 85.4%. Subsequently, we maximized specificity and reported a seroprevalence, based on more than one antigen, ranging from 9.3% to 25.9%. Conclusions: This study revealed the importance of evaluating serosurvey tools for antigen-, isotype-, and threshold-specific sensitivity and specificity, to interpret qualitative serosurvey outcomes reliably and consistently across studies. Abstract : This cross-sectional study tested how antigen, isotype, and threshold choices affected severe acute respiratory syndrome coronavirus 2 seroprevalence outcomes based on a laboratory-developed enzyme-linked immunosorbent assay and found that compound estimate-based outcomes were most reliable when specificity was maximized.